On the interplay of elastic anisotropy and fracture toughness anisotropy in fracture of single and multiphase polycrystals. (1st October 2022) - Hirshikesh, Hirshikesh; Alankar, Alankar
Abstract: This work presents a phase field model (PFM) for understanding crack propagation in a brittle polycrystalline material during quasi-static loading. A parametric study is performed by varying the elastic anisotropy and the fracture toughness anisotropy. The fracture toughness anisotropy is defined as a function of misorientation between neighboring grains and elastic anisotropy as a function of single crystal elasticity coefficients. The grain boundary fracture toughness is degraded compared to the grains within the PFM. This approach allows modeling intergranular and transgranular crack growth physically informed by the grain structure. A series of numerical simulations of single crystals, bicrystals, and polycrystals are performed to decouple the effects of elastic anisotropy and fracture toughness anisotropy on crack propagation. The model agrees well with similar studies found in the literature. In addition, the proposed PFM formulation is applied to simulate fracture in dual phase brittle polycrystals and the effect of the arrangement of phases on the overall fracture toughness of a polycrystal. Highlights: Analyses of the role of elastic anisotropy and fracture toughness anisotropy on crack path. Modeling the effect of grain boundary fracture toughness on intra-granular vs. inter-granular cracks. A combined analysis using single crystals, bicrystals and polycrystals. Effect of material phases on crack path and overall fracture-toughness of polycrystals.